The Effect of Parents’ Schooling on Child’s Schooling: A Nonparametric Bounds Analysis - de Haan, Monique (Journal of Labor Economics, 2011)
A positive relation between parents’ schooling and child’s schooling does not necessarily reflect a causal relation. This article uses a new approach to identify intergenerational schooling effects: a nonparametric bounds analysis. By relying on relatively weak and in part testable assumptions, this article obtains informative bounds on the average causal impact of parents’ schooling. The tightest bounds, using monotone instrumental variables, show that increasing mother’s or father’s schooling to a college degree has a positive effect on child’s schooling that is significantly different from zero but substantially lower than the ordinary least squares estimates.